International Responses to Health Epidemics: An Analysis of Global Health Actors' Responses to Persistent Cholera Outbreaks in Harare, Zimbabwe. - Nyaruwata, Chido (Department of Political Studies, 2020)
Cholera is a diarrhoeal disease caused by the infection of the intestine with bacterium vibrio cholera. The diarrhoeal disease is a recurrent feature of Zimbabwe's post 1990s history. From 1993 to 2018, the country has experienced several cholera outbreaks in both rural and urban areas. The country's worst cholera outbreak occurred in 2008/2009 and resulted in over 4000 deaths. The dissertation analyses three global health actors' responses to persistent cholera outbreaks in Harare, the capital city of Zimbabwe. Building on previous scholarship of water, cholera and politics, the dissertation compares global health actors' responses to the 2008/2009 and September to November 2018 cholera outbreaks. The dissertation used the qualitative research method including analysis of existing academic literature, Zimbabwean national legislation, non-governmental organisation (NGO) publications and conference reports, news articles and Zimbabwean government policy documents. In-depth interviews with personnel from the World Health Organisation, United Nations Children's Fund, Médecins Sans Frontierès (Doctors without Borders) and the Harare City Council Health Department were conducted in Harare, Zimbabwe from June to July 2019. The dissertation demonstrates that the scope and speed of global health actors' emergency cholera interventions in Harare are shaped by Zimbabwe's political climate and the state of Harare's health, water and sanitation infrastructure.